Thromboangiitis obliterans: Aggressive angioplasty provides a potential solution (randomized pilot study) - Mosaad Soliman; Khaled Mowafy; NA Elsaadany; Reem Soliman; Ahmed Elmetwally (SAGE Open Medicine, 2020)
Background: Thromboangiitis obliterans is an inflammatory disease affecting both medium- and small-sized vessels. Vasodilators, antiplatelets were proposed for treatment but the effect was minimal. Objective: This study was conducted to investigate the effect of balloon angioplasty on patients with Buerger’s disease compared to medical treatment. Methods: Between January 2006 and December 2016, 82 patients with Buerger’s disease were enrolled in the study, of whom 52 were randomized to the aggressive endovascular intervention and 30 were randomized medically by cilostazol and aspirin as a control group. In all, 23% of the patients presented with severe claudication, 50% with ischemic rest pain and 27% with ischemic ulcers. Randomization was done using the opaque envelope method. Allocation concealment was maintained to ensure no selection bias. Patient groups were compared for the duration of ulcer healing, ankle–brachial index, peak systolic velocity changes and transcutaneous oximetry (TcPO2) level for 30 months. Results: No major procedural complications occurred in the endovascular group. Angiographic success was achieved in 100% of supragenicular lesions but in 90% of infrapopliteal lesions. The endovascular group showed a statistically significant improvement in the ulcer healing size and duration at 6 months after the procedure with a mean time of 3 ± 0.9 months compared to 5.8 ± 1.69 months for the medical treatment group (p < 0.001), the mean TcPO2 from 27.23 ± 16.75 mm Hg (range: 0–56 mm Hg) before the procedure to 71.32 ± 12.94 mm Hg (range: 52–92 mm Hg) following revascularization (p < 0.01). The mean ankle–brachial index significantly improved from 0.54 ± 0.14 preoperatively to 0.82 ± 0.08 at final follow-up (p < 0.01). Conclusion: The endovascular therapy should be considered as an effective, safe, minimally invasive method in the light of the promising results after a modification of the standard technique.